A new combination in Wedelia (Asteraceae-Heliantheae-Ecliptinae) from Brazil - Remor, Danielle; Bernardo De A. Bringel Jr., João; Floriano B. Pastore, José (Phytotaxa, 2022)
An overlooked name Aster monanthus, described in Vellozo’s Flora Fluminensis, is here revised and transferred to the genus Wedelia, as W. monantha. Field trips to the most likely original locality for Aster monanthus (Estrada Real in the Cunha municipality of São Paulo state, Brazil), along with a revision of herbarium specimens, were made. A full species description, with a distribution map and taxonomic notes, is provided. All relevant names have been lectotypified and an epitype for Vellozo’s name chosen.